Picture perfect food : master the art of food photography with 52 bite-sized tutorials - Simon, Joanie (Salem Massachusetts : Page Street Publishing, 2021)
Snapping unbelievably gorgeous food photos has never been simpler than with Picture Perfect Food, your all-in-one guide to delicious-looking images from prolific photographer and educator, Joanie Simon. Whether you're an up-and-coming food blogger, looking to break into commercial photography or capturing food just for fun (and your Instagram account), this approachable collection of tutorials will have you taking tantalizing and tasty shots with every snap of the shutter.
Introduction -- Camera settings -- Light and shadow -- Story -- Props styling -- Composition -- Food styling -- Finding inspiration.
Includes index.
Keywords: FOOD PRESENTATION